As relações e os desdobramentos da dupla avaliação (CEE/GO e Sinaes) na administração central da Universidade Estadual de Goiás - Campos, Valter Gomes (2019)
This study is part of the field of higher education, in the subfield of institutional evaluation, and aims to analyze the results of the double evaluation (CEE/GO and Sinaes) in the State University of Goiás (UEG) central administration. The research sought to capture what moves the individual and collective agents, who in relations, participate in the constitution of the institutional evaluation habitus, which has a close connection with the managerial habitus of the University. In this sense, it was taken as a cut and sought to be understood the association of the double evaluation with the resolutions of the higher collegiate bodies and with the decisions and actions of the central administration, in the period from 2011 to 2017. From the bibliographical readings and theories used emerged the following categories of analysis: relations, field, habitus, capital, symbolic violence, totality, contradiction and historicity. The work is characterized as a case study, with bibliographical, documentary and field research, which through this broad approach sought to understand the object of study in its totality. For the analysis and understanding of the object, the study was based on the contributions of Pierre Bourdieu and the works of authors of the field of higher education and the subfield of institutional evaluation, among others, Catani, Oliveira, Dourado and Dias Sobrinho. The following results are worth highlighting: the demonstration of the adherence to the political field defining the managerial habitus and assessment of UEG; the proof of the double and mixed evaluation demonstrated by the evaluation processes (CEE/GO and Sinaes) taken jointly, often as sides of the same coin, but with Sinaes as official guider and reference for actions of evaluation and regulation of CEE/GO; the use of the evaluation processes results, in particular the scores of Enade, the CPC and the IGC to support the resolutions and decisions of UEG central administration, changing the habitus of UEG assessment and management; the search for the improvement of these grades and indexes as an expression of the quality of the courses and of the Institution, which together with the financing, budgetary and financial issues set the tone for the planning and decisions of UEG central administration in the covered period; The study also revealed that the concern with ranking is due to the quest for distinction and positioning in the field of higher education, which, in turn, becomes an element for evaluation of the institution's own central administration and for the benefit of managers’ relationships with internal and external communities, especially with political field and the state government. Finally, checked that as an internalized structure, the ranking and positioning in the field are incorporated into the way of using the double institutional evaluation and its unfolding in the University central administration, externalized as practices, discourses and relations between the internal and external agents of the Institution.